A miniaturized solid contact test with Arthrobacter globiformis for the assessment of the environmental impact of silver nanoparticles. (21st March 2014) - Engelke, Maria; Köser, Jan; Hackmann, Stephan; Zhang, Huanjun; Mädler, Lutz; Filser, Juliane
Abstract Silver nanoparticles (AgNPs) are widely applied for their antibacterial activity. Their increasing use in consumer products implies that they will find their way into the environment via wastewater‐treatment plants. The aim of the present study was to compare the ecotoxicological impact of 2 differently designed AgNPs using the solid contact test for the bacterial strain Arthrobacter globiformis. In addition, a miniaturized version of this test system was established, which requires only small‐sized samples because AgNPs are produced in small quantities during the design level. The results demonstrate that the solid contact test can be performed in 24‐well microplates and that the miniaturized test system fulfills the validity criterion. Soils spiked with AgNPs showed a concentration‐dependent reduction of Arthrobacter dehydrogenase activity for both AgNPs and Ag ions (Ag+). The toxic effect of the investigated AgNPs on the bacterial viability differed by 1 order of magnitude and can be related to the release of dissolved Ag+. The release of dissolved Ag+ can be attributed to particle size and surface area or to the fact that AgNPs are in either metallic or oxide form. Environ Toxicol Chem 2014;33:1142–1147. © 2014 SETAC